Dynamic Improving Energy Efficiency in Automotive Electrical ‎Equipment (Journal of University of Babylon for Engineering Sciences, 2025)
This paper examines the advancements in energy efficiency for three-phase squirrel cage induction motors (SCIM), the leading segment in the electric motor market. It highlights the development of SCIMs that meet IE4efficiency standards using standard frame sizes and aluminum rotor cages, emphasizing the historical use of copper for achieving IE3 standards and reducing rotor inertia. Additionally, the paper discusses other IE4 class motors such as Line Start Permanent Magnet (LSPM) motors with interior rare-earth permanent magnets and auxiliary cages for starting, as well as Variable Reluctance Synchronous Motors (VRSM) and Switched Reluctance Motors (SRM). The SCIM IE4 motor, with its cost-effective aluminum cage, is particularly suitable for large-scale industrial use due to its production costs, starting torque, and synchronization capabilities. The article also explores the potential market growth for LSPMs if their capabilities are enhanced to meet IE5 standards. Furthermore, it discusses the impact of national and regional standards on motor frame sizes and the challenges faced by manufacturers in reducing losses to improve efficiency. Through a comprehensive analysis of materials, design optimizations, and cutting-edge manufacturing techniques, the article provides insights into achieving higher efficiency in electric motors.